Application of multiplexing fiber optic laser induced fluorescence spectroscopy for detection of aflatoxin B1 contaminated pistachio kernels. (30th August 2019) - Wu, Qifang; Xu, Huirong
Highlights: Multiplexing fiber optic LIFS was used for detection of AFB1 contaminated pistachios. The 390–660 nm had important contribution for classifying AFB1 contaminated kernels. Best screening ability was obtained by three-probe LIFS system. Abstract: To explore the effect of signal acquisition way on screening ability, the multiplexing fiber optic laser induced fluorescence spectroscopy (LIFS) system with one-, two- and three-probe, were employed respectively to detect artificially aflatoxin B1 (AFB1, 5, 10, 20, 30, and 50 ppb) contaminated 300 pistachio kernels in this study. Compared to one- and two-probe modes, highest accuracy (≥97.0%) by support vector machine (SVM) employing 390–660 nm were obtained using three-probe, which also showed the most attractive precision (root mean square error of prediction (RMSEP) < 4.5 ppb) for AFB1 by stepwise multiple linear regression (SMLR) using 174–1100 nm. These suggested that the effective collection of spatial information could improve the performance of model, and the three-probe LIFS had a preliminary feasibility for discriminating pistachios contaminated with low concentration of AFB1 . Further study on classifying naturally contaminated samples is needed to validate the applicability of this system.